Efek Budaya Kerja terhadap Remunerasi Tenaga Kependidikan - Sukri Katili (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2023)
The study explores the impact of work culture for remuneration. Correlational research design was adapted to work culture and remuneration of support staff. Data was obtained from a sample of 254 non-teaching staff that were randomly selected from twenty one units working of the Universitas Negeri Gorontalo. Seventy two non-teaching staff schools were identified using stratified random sampling and purposive sampling methods using the Slovin formula. Data collection instruments such as questionnaires, observation, interview and documentation were administered. Furthermore, the collected data were analyzed using descriptive and inferential analyses. The findings indicate that work culture contributes to remuneration significantly (p < 0.05) with the percentage of 18.44%. the better the quality of remuneration education staff.Penelitian ini bertujuan untuk mengetahui pengaruh langsung budaya kerja terhadap remunerasi tenaga kependidikan. Penelitian dilaksanakan di Universitas Negeri Gorontalo dengan jumlah populasi sebanyak 254 orang, sedangkan Perhitungan besaran sampel (sample size) dilakukan dengan menggunakan formula yang dikemukakan oleh Slovin yaitu berjumlah 72 orang. Teknik pengumpulan data yaitu angket, wawancara dan studi dokumentasi. Analisis data menggunakan analisis deskriptif dan analisis inferensial. . Hasil penelitian menunjukkan bahwa terdapat pengaruh remunerasi terhadap budaya kerja tenaga kependidikan sebesar 18,44%, maka budaya kerja memiliki pengaruh terhadap penerimaan remunerasi tenaga kependidikan.